Comparison of Physiochemical, Biochemical and Antimicrobial Properties of Natural and Artificial Apis mellifera L. Beeswax - Ertürk, Ö; Keskin, M; Birinci, C; Kolaylı, S (Journal of the Hellenic Veterinary Medical Society, 2024)
The interest in bee products is increasing day by day. Beeswax is the honeycomb cells in which bees store their honey. Due to their rich biocompenents, it has both antioxidant and antimicrobial activity. Beeswax could be produced naturally by bees as well as it is commercially available. Commercial beeswax is processed by bees and get ready for honey storage. In this study, the physicochemical properties of commercial and natural beeswax such as water vacuum capacity, oil content, oral secretion and elemental composition were identificated. Then, the beeswax was extracted using different solvents, biochemical and antimicrobial activities of these samples were compared. Natural beeswax was found to have less water absorption capacity, higher oil content (52.79±0.12%) and contained more plant material. Y-acetone extract of beeswax had higher total phenolic content (3.74±0.03 mg GAE/g) and showed a good antioxidant activity (70.23±1.30 µM FeSO4.7H2O/g) than other extracts prepared different solvents. It was clear that both extracts had a good antimicrobial activity. Y-methanol extract was found to be effective on B. subtilis and M. luteus, D-ethanol on E. coli, Y-ethanol on L. monocytogenes, and Y-acetone on P. vulgaris. It was clear that both artificial and natural beeswax could be used in different applications in a wide range food to medicine.